The influence of fundamental factors on stock price in food and beverage subsector companies listed on the IDX for the 2017-2021 period - Nur Avanti, Yuhilma; Putra, Syailendra Eka (Review of Management, Accounting, and Business Studies, 2022)
This study aims to specify:  To analyze the effects of leverage, liquidity, and profitability on stock prices of food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This type of research is descriptive and associative research. The population of this study are Food and Beverage Companies listed on the Indonesia Stock Exchange for the range of 2017-2021 period. The sampling technique used was Total Sampling with a total sample is 15 companies. Data analysis used the t-test and F-test, assisted by Reviews program version 8. The results showed that: Leverage has no significant effects on stock prices. Liquidity has no significant effect on stock prices. Profitability has a significant effect on stock prices. Leverage, Liquidity, and Profitability together have significant effects on Stock Prices.